Manajemen Kegiatan Organisasi Kesiswaan dan Ekstrakurikuler dalam Pengembangan Karakter Peserta Didik di SMP Mu’allimin Mu’allimat Pondok Pesantren Gedongan Cirebon - Didit Rahadiat; Zakaria Z (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Student organization and extracurricular activities are far more than a filler in the school timetable, they serve as a growth space for character, leadership, and social competence, particularly within pesantren-based institutions where academic demands, religious instruction, and boarding life must be balanced all at once. This article draws on a study examining the management of student organization and extracurricular programs at SMP Mu’allimin Mu’allimat, Pondok Pesantren Gedongan, Cirebon, guided by three questions, namely how the management system is applied, what forms of student involvement exist and how they affect character development, and what challenges arise along with the managerial strategies used to address them. A descriptive qualitative approach was employed, relying on participatory observation, semi-structured interviews, and documentation, with data analyzed through the Miles and Huberman interactive model and validated through source, technique, and theory triangulation. Findings reveal that activity management runs through three stages, participatory planning, implementation woven into students’ daily routines, and periodic evaluation, all consistently anchored in Islamic values. Student participation is notably high, reaching around ninety two percent, and produces tangible outcomes in confidence, responsibility, teamwork, and spiritual depth. At the same time, the school continues to grapple with limited facilities, funding, and time, which are addressed through maximizing open spaces, external collaboration, and early scheduling.